2019
DOI: 10.5483/bmbrep.2019.52.2.129
|View full text |Cite
|
Sign up to set email alerts
|

OAS1 and OAS3 negatively regulate the expression of chemokines and interferon-responsive genes in human macrophages

Abstract: Upon viral infection, the 2′, 5′-oligoadenylate synthetase (OAS)-ribonuclease L (RNaseL) system works to cleave viral RNA, thereby blocking viral replication. However, it is unclear whether OAS proteins have a role in regulating gene expression. Here, we show that OAS1 and OAS3 act as negative regulators of the expression of chemokines and interferon-responsive genes in human macrophages. Clustered regularly interspaced short palindromic repeats (CRISPR)-CRISPR-associated protein-9 nuclease (Cas9) technology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…However, preliminary evidence for the existence of a cross-regulatory interaction between ZAP and RNAseL/OAS3 might include the observation that ZAP k/o leads to much greater constitutive expression of RNAseL (Figure 13B). Conversely, OAS3 k/o leads to an upregulation of ISG expression activated through MAVS (67). However, further work is needed to disentangle direct effects between these antiviral pathways and effects mediated through differences in interferon induction and secondary activation of ZAP, OASs and RNAseL expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, preliminary evidence for the existence of a cross-regulatory interaction between ZAP and RNAseL/OAS3 might include the observation that ZAP k/o leads to much greater constitutive expression of RNAseL (Figure 13B). Conversely, OAS3 k/o leads to an upregulation of ISG expression activated through MAVS (67). However, further work is needed to disentangle direct effects between these antiviral pathways and effects mediated through differences in interferon induction and secondary activation of ZAP, OASs and RNAseL expression.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 OAS3 can synthesize 2 0 , 5 0 -oligoadenylates (2-5A) from ATP on binding to double-stranded (ds)RNA and is specialized for binding long dsRNA. 21 OAS3 activates RNase L endonuclease in response to FIGURE 3. Location and conservation of mutated amino acid residue, and the expression of OAS3.…”
Section: Discussionmentioning
confidence: 99%
“…exogenous RNA from either virus or bacteria, [21][22][23][24] suggesting that the OAS/RNaseL pathway is a major antiviral defense mechanism. [21][22][23][24][25] Recent research revealed that OAS3 could activate RNase L and inhibited ZIKA virus replication. 26 Therefore, OAS3 mutation enhances the host's susceptibility to viral or bacterial infection, which in turn, activates their inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The 2′-5′-oligoadenylate synthetase 1 (OAS1) belongs to the OAS family, which inhibits cellular protein synthesis and resistance to viral infection (35). Lee et al (36) demonstrated that OAS1 negatively regulates the expression of chemokines and interferon-responsive genes in human macrophages. Literature search results did not reveal any association between OAS and the carcinogenesis or progression of tumors; thus suggesting that ES occurrence may be associated with OAS1, but further investigations are required.…”
Section: Discussionmentioning
confidence: 99%